Federal Regulation and Mortality in the 50 States. Issue 3 (23rd June 2021) - Broughel, James; Chambers, Dustin
Abstract: Previous research speculates that some regulations are counterproductive in the sense that they increase (rather than decrease) mortality risk. However, few empirical studies have measured the extent to which this phenomenon holds across the regulatory system as a whole. Using a novel U.S. state panel data set spanning the period 2000–2014, we estimate the effect of U.S. federal regulation on state‐level mortality. We find that a 1% increase in federal regulation of state economies is associated with an increase in an index of state mortality of between 0.53% and 1.35%. These findings are robust to the form of mortality measure, choice of covariates, and the inclusion/exclusion of various regions, states, and industries. We also provide an update of the "cost‐per‐life saved cutoff, " which is the counterproductive risk threshold for expenditures. We find that expenditures in excess of $38.6 million (2019 dollars) per life saved can be expected to increase mortality risk. This article fills an important gap in the empirical literature and boosts the credibility of mortality risk analysis, whereby public policymakers weigh both the expected lives saved and lost due to a proposed regulation or other policy.